Caracterización de la dimensión de los servicios turísticos en la provincia El Oro. Ecuador - Raúl López Fernández; Ana Vanessa Maldonado Córdova; Jessica Lalangui Ramírez (Revista Metropolitana de Ciencias Aplicadas)
The basic tourist services are important for the development of this activity anywhere in the world because they facilitate comfort for tourists. The objective of this research is to characterize the basic tourist services in the province El Oro of Ecuador for the achievement of a sustainable development. A correlational longitudinal descriptive observational study was developed, where the scenario used were the tourist areas and the sample is made up of national and foreign tourists who visited the region. The methods used were, the synthetic analytical and the inductive deductive and in practical, the survey, from the mathematical and statistical point of view, the measure of tendency centers median, charts of boxes and whiskers and Cronbach's alpha. The fundamental results were that the medians were above seven and the correlation among the variables of the instrument required a good Cronbach's alpha. It can be concluded that the basic services of: water, garbage, medical tourism, among others, were dotted with very good ones, which guarantees in the Province El Oro, a tourist destination of national reference.